2018
DOI: 10.1080/09712119.2018.1450751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary guanidinoacetic acid and betaine supplementation on performance, blood biochemical parameters and antioxidant status of broilers subjected to cold stress

Abstract: This study was conducted to determine the effects of dietary guanidinoacetic acid (GAA) and betaine supplementation on performance, antioxidant status and biochemical parameters of broilers subjected to cold stress. Based on a 2 × 2 factorial arrangement, 384-day-old male broiler chicks (Cobb) were randomly distributed between four experimental diets (with 8 replicates and 12 birds per replicate) included basal diet (as control) and the basal diet supplemented with 1200 mg/kg GAA; 600 mg/kg betaine and 1200 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…Studies that investigate the effect of GAA on antioxidant systems in poultry are limited. Recently, in agreement with our results, Nasiroleslami et al (2018) reported an increase in liver GSH-Px activity and a reduction in serum MDA content as the addition level of GAA increased to 1.2 g/kg of broiler diet. Also, by 0.8, 1.2 and 2 g/kg of GAA supplementation in pig diet, Wang et al (2012) observed a quadratic increase in antioxidant enzymes activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies that investigate the effect of GAA on antioxidant systems in poultry are limited. Recently, in agreement with our results, Nasiroleslami et al (2018) reported an increase in liver GSH-Px activity and a reduction in serum MDA content as the addition level of GAA increased to 1.2 g/kg of broiler diet. Also, by 0.8, 1.2 and 2 g/kg of GAA supplementation in pig diet, Wang et al (2012) observed a quadratic increase in antioxidant enzymes activity.…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that GAA may also play antioxidant and pro-oxidant properties depending on concentration and route of administration. In broiler, dietary GAA supplementation had increased liver glutathione peroxidase activity and decreased serum MDA level (Nasiroleslami et al 2018). However, pathological accumulation of GAA can induce oxidative stress, as shown by decreased total radical-trapping antioxidant potential, total thiol content and antioxidant enzymes activity following intrastriatal infusion in rats (Zugno et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Although the current research did not record considerable differences in the liver GSH levels between different experimental groups, the GAA supplements resulted in a significant reduction in the liver MDA levels. Consistent with these results, Nasiroleslami et al (2018) reported that the dietary supplementation of 1200 mg/kg GAA significantly decreased the serum MDA level in broilers subjected to cold stress. In growing-finishing pigs, Wang et al (2012) had reported that a higher dosage of dietary GAA supplements increased the total antioxidant capacity, with an eventual reduction in the plasma MDA level.…”
Section: Discussionsupporting
confidence: 77%
“…MDA, a main end product of lipid peroxidation, has been widely used as an indicator of oxidative damage and meat quality (Alirezaei et al, ). Previous studies have reported the positive effects of betaine on oxidative status (Alirezaei et al, ; Alirezaei, Jelodar, Niknam, Ghayemi, & Nazifi, ; Nasiroleslami, Torki, Saki, & Abdolmohammadi, ). In this study, betaine supplementation linearly decreased the content of MDA and linearly increased the activities of T‐SOD and CAT in breast muscle of ducks.…”
Section: Discussionmentioning
confidence: 94%
“…Lipid peroxidation is one of the most important causes of the deterioration of meat quality, which will decrease meat nutritive value and lead to flavour problems (Fernández, Pérez-Álvarez, & Fernández-López, 1997;Salih, Smith, Price, & Dawson, 1987). MDA, a main end product of lipid peroxidation, has been widely used as an indicator of oxidative damage and meat quality (Alirezaei et al, TA B L E 7 Effect of betaine on the antioxidant activity in breast muscle of ducks at 42 days of age (Alirezaei et al, 2012;Alirezaei, Jelodar, Niknam, Ghayemi, & Nazifi, 2011;Nasiroleslami, Torki, Saki, & Abdolmohammadi, 2018). In this study, betaine supplementation linearly decreased the content of MDA and linearly increased the activities of T-SOD and CAT in breast muscle of ducks.…”
Section: Discussionmentioning
confidence: 99%